The handbook of project management - Huemann, Martina 1969-; Turner, J. Rodney (John Rodney) 1953-; Turner, J. Rodney (John Rodney) 1953- (London Routledge, Taylor & Francis Group, 2024)
"This practice-oriented handbook presents practitioners and students with a comprehensive overview of the essential knowledge and current best practice in project management. It includes the most up-to-date thinking in the discipline, describing recent developments in a way that practitioners can immediately use in their work. The Handbook of Project Management was the first "APM Body of Knowledge Approved" title for the Association for Project Management. Over the course of six editions, the Handbook of Project Management has become the definitive desk reference for project management practitioners. The team of expert contributors, selected to introduce the reader to the knowledge and skills required to manage projects, includes many of the most experienced and highly regarded international writers and practitioners. The book is divided into six parts: Projects; Performance; Process; People, Portfolio; and Perspectives. Including over 25 completely new chapters, this sixth edition provides a fully up-to-date encyclopaedia for the discipline and profession of project management. The book will be of use to all project management practitioners, from those starting out in the profession to people with advanced experience. It is also highly relevant to students, with earlier editions being used as a set or recommended text on Masters' courses in project management"--
Includes bibliographical references.
Keywords: Project management; Project management -- Handbooks, manuals, etc